IDENTIFIKASI CENDAWAN TERBAWA BENIH PADI DARI KECAMATAN CIRUAS KABUPATEN SERANG BANTEN - Andree Saylendra (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2010)
ABSTRACT The objective of this experiment was conducted to identification of seed-borne fungi that infected or contaminated paddy seed. Paddy seed samples were collected from sub district of Ciruas, Serang, Banten. Eighty hundred seeds used by random sampling method as the work sample in seed health testing were obtain from 8200 gram of the sample that collected from 82 group of farmer. Testing method that been used were blotter test and agar test. Thirty genera of fungi were found from this experiment. They were Rhizopus, Fusarium, Mucor, Alternaria, Drechslera, Pythium, Botrytis, Penicillium, Aspergillus, Cercospora, Cercosporella, Trichoderma, Colletotrichum.Keywords : identification, fungi, paddy, seed-borne